PENGARUH SHOPPING LIFE STYLE DAN FASHION INVOLVMENT TERADAP IMPULSE BUYING BEHEVIOR MASYARAKAT HIGH INCOME MAKASSAR - Sani, Amar; Hafidah, Andi (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
The dynamics of the real business economy in Indonesia shows a very rapid growth so that it will trigger the development of the lifestyle and spending patterns of the people (consumers) who have higher expectations, more needs, and a better and more consistent quality of life. The problem faced is that high income customers show patterns of expenditure and fluctuations, often miss the financial planning that has been made. This study aims to prove the effect of shopping life style and fashion involment on Behevior's impulse buying behavior in the Makassar High Income community. This study uses a sample who lives in urban communities, has their own income, has an expenditure of approximately 2,500,000, has shopped at M-Tos, Mall Panakukang, MTC, GTC, and Karebosi Link. The analysis technique used is multiple linear regression, which will make it easier to see the effect of shopping life style and fashion involment on Behevior's impulse buying behavior in the Makassar High Income community who will be tested. The resulting output scientific journals.